Firewalls jumpstart for network and systems administrators - Vacca, John R. (Elsevier Digital, 2005)
In this book, you will gain extensive hands-on experience installing and configuring a firewall. You will also learn how to allow access to key Web services while maintaining your organization's security, as well as how to implement firewall-to-firewall virtual private networks (VPNs). You will learn how to build a firewall to protect your network; provide access to HTTP and FTP services on the Internet, and implement publicly accessible servers without compromising security. Furthermore, throughout the book, extensive hands-on examples provide you with practical experience in establishing security with firewalls. Examples include, but are not limited to: Installing and configuring Check Point FireWall-1; scanning to validate configuration using ISS Internet Scanner; configuring the firewall to support simple and complex Web services; setting up a packet filtering router; enhancing firewall configurations to support split-DNS; authenticating remote users; and protecting browsers and servers with a proxy-based firewall. Install and configure proxy-based and stateful-filtering firewalls Protect internal IP addresses with NAT and deploy a secure DNS architecture Develop an Internet/intranet security policy to protect your organization's systems and data Reduce your susceptibility to an attack by deploying firewalls, data encryption and decryption and other countermeasures.